Odpowiedź :
Odpowiedź:
f) odp : y * y - 2y + y - 2 = [tex]y^{2}[/tex] - 2y + y - 2 = [tex]y^{2}[/tex] - y - 2
g) odp ; ab * b + 4ab + 2b +2 * 4 = a[tex]b^{2}[/tex] + 4ab + 2ab + 8
h) odp : -[tex]x^{2}[/tex] * 5x - [tex]x^{2}[/tex] - 3 * 5 * -3 = -5[tex]x^{3}[/tex] - [tex]x^{2}[/tex] - 15x - 3
i) odp : 2[tex]x^{2}[/tex] * x - 2[tex]x^{2}[/tex] * 3 + 3x - 3 * 3 = 2[tex]x^{3}[/tex] - 6[tex]x^{2}[/tex] + 3x - 9
j) odp : [tex]x^{2}[/tex]y * 2x -2[tex]x^{2}[/tex]y +2 * 2 * - 2 * 2 = 2[tex]x^{3}[/tex]y - 2[tex]x^{3}[/tex]y + 4 * -4
k) odp : -x * 5x -11x - 6*5x - 6 * 11 = -5[tex]x^{2}[/tex] - 11 = -5[tex]x^{2}[/tex] - 11x - 30x - 66 = -5[tex]x^{2}[/tex] -41x - 66
Szczegółowe wyjaśnienie:
Dasz Nailepszy Odpowiedź :) starałem sie